Sphingosine 1-phosphate pathway is dysregulated in adenomyosis. Issue 1 (July 2022) - Vannuzzi, Valentina; Bernacchioni, Caterina; Muccilli, Angela; Castiglione, Francesca; Nozzoli, Filippo; Vannuccini, Silvia; Capezzuoli, Tommaso; Ceccaroni, Marcello; Bruni, Paola; Donati, Chiara; Petraglia, Felice
HIGHLIGHTS: S1P is a key molecule in fibrosis, proliferation, and inflammation. S1P axis is involved in adenomyosis and could be an innovative biomarker. mRNA levels of S1P pathway molecules are dysregulated in adenomyosis. Abstract: Research question: Is sphingosine 1-phosphate (S1P) pathway involved in the process of fibrosis in adenomyosis? Design: RNA was extracted from paraffin-embedded slices collected from the ectopic endometrium of patients with nodular adenomyosis ( n  = 27) and eutopic endometrium of healthy controls women ( n  = 29). Expression of genes involved in the metabolism and signalling of S1P, and actin-alpha-2 smooth muscle, encoded by ACTA2 gene, a gene involved in fibrogenesis, was evaluated by real-time polymerase chain reaction analysis. Results: In adenomyotic samples, the expression of sphingosine kinase 1 ( SPHK1 ), the enzyme responsible for the synthesis of S1P, and of S1P phosphatase 2 ( SGPP2 ), the enzyme responsible for the conversion of S1P back to sphingosine, was lower ( P  = 0.0006; P  = 0.0015), whereas that of calcium and integrin-binding protein 1, responsible for membrane translocation of SPHK1, was higher ( P  = 0.0001) compared with healthy controls. In S1P signalling, a higher expression of S1P receptor S1P3 ( P  = 0.001), and a lower expression of S1P2 ( P  = 0.0019) mRNA levels, were found compared with healthy endometrium. In adenomyotic nodules, a higher expression of ACTA2 mRNA levels were observed ( P  = 0.0001), which correlated with S1P3 levels ( P  = 0.0138). Conclusion: Present data show a profound dysregulation of the S1P signalling axis in adenomyosis. This study also highlights that the bioactive sphingolipid might be involved in the fibrotic tract of the disease, correlated with the expression of ACTA2, suggesting its role as novel potential biomarker of adenomyosis.